Practice of Discovery Learning Model in Elementary Schools - Paputungan, Frezy; Masaguni, Ririn (Indonesian Journal of Social Science and Education (IJOSSE), 2025)
This study aims to determine the use of quiziz in fifth grade elementary school students at SDN 7 Bulango Selatan. This study aims to provide simple and clear guidance for school teachers, prospective teachers, and also subject teachers in compiling lesson plans using Game Based Learning. Although there are many books, articles, and other sources that discuss it, it is still an obstacle for some teachers in compiling lesson plans. Based on the author's experience in teaching students, it seems difficult to plan Discovery Learning syntax systematically and organize class activities appropriately in each syntax. They sometimes cannot distinguish the syntax of the method from others, even though this method is one of the suggested and recommended methods and has been widely used. To help students and teachers, this article supports them with a clear definition along with its systematic syntax, advantages and disadvantages